WATER EROSION TREATMENT LINEAR-VERTEBRATE PLUG - Rashidov Nurbek son of Shermamat; Temirov Isroil Gulomovich (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Today, the development and application of soil treatment machines with high soil protection energy-resurstejamkor and work performance are at the forefront. 31% of the land is affected by water erosion, and 34% by wind erosion, and 60 crore annually.considering that more than a ton of the fertile layer of soil is washed away, energy-resource-intensive soil treatment, which protects the soil from water and wind erosion, is one of the important tasks for the development of machines and weapons. Sufficiently insoluble soil particles in water contribute to the occurrence of water and wind erosion, the transformation of the soil surface into small particles and the destruction of soil residues, it leads to a decrease in its ability to collect moisture. Erosion by water and wind absorbs the fertile part of the soil and accelerates the onset of soil drought. The result was a blunderbuss with a butt structure, a shaped warhead, and the ability to withstand a load [1,2]. Data and their assumption: as you know, lalmikor farming occupies an important place in the economy of Uzbekistan. In our republic, lalmikor farmable soils are worth 2 million. 130,000 hectares. The area of the Lalmikor maydans is 801.45 thousand hectares, including the maydans located in the Crimea The Reserve (235.5 thousand ha.), Jizzakh (204.5 thousand ga.) and Samarkand (193.9 thousand ha.) per province. Lalmi farming is done on sloping land in most HAVs[1].